PENERAPAN METODE JUST IN TIME SEBAGAI UPAYA MENINGKATKAN EFESIENSI BIAYA PERSEDIAN BAHAN BAKU PT CITRA ADILANCAR - Nuzul Eky Fachrezy; Dika Aprian Fratama; Resa Aulia Febriansyah; Widya Setiafindari (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This study aims to evaluate the inventory control system of PT Citra Adilancar which can minimize inventory costs by comparing the company's total inventory cost system. So a research was carried out using the Just In Time method to reduce excess raw materials and the kanban method to expedite the Just In Time course so that there is no excess raw material anymore. The objects of this research were plate raw materials, holo iron, angle iron, resin, talc, fiber, catalyst and putty with several variables. The dependent variable is optimal raw material inventory and minimum total inventory cost, while the independent variables are raw material inventory data, raw material ordering costs, holding costs, demand data, and ordering data. The method used in this study is the Just In Time and Kanban method, which can reduce excess raw materials and produce on time. With the storage method the company has a total inventory cost of Rp. 213,130,000. The inventory system with the Just In Time method has a total cost of Rp. 183,967,500. From the results of these calculations, the minimum inventory cost is obtained using the Just In Time method. And make related proposals to change the inventory control system. To create an accurate Just In Time system, a kanban card is then designed.